Study on the fabrication of CdZnSe/ZnSeS ternary alloy quantum dots. (9th March 2015) - Nga, Pham Thu; Yen, Nguyen Hai; Cuong, Dinh Hung; Hai, Nguyen Ngoc; Nghia, Nguyen Xuan; Hanh, Vu Thi Hong; Vu, Le Van; Coolen, Laurent
In an effort to search for new compositions and structures of quantum dots with suppressed blinking photoluminescence (random switching between states of high (on) and low (off) emissivity under continuous photo–excitation) and to serve application purposes in biosensors and in optoelectronic devices, we have studied the fabrication of new CdZnSe/ZnSeS ternary alloy quantum dots (QD). In this work, we present new results on the fabrication of the alloy core/shell quantum dots having a shell thickness of about 1.52 nm and a varied shell composition in Se#47;S ratio. The influence of the growth temperature on the structural properties (crystalline phase and cell), size and elemental compositions of the core and core/shell QDs is presented. Analysis and in–depth comparison of the calculated ternary QDs' composition are performed based on the energy dispersive X–ray spectroscopy (EDS) data and the first exciton absorption peak position and size. Interpretation of the experimental results is also provided.